PRIVATE INTERNATIONAL LAW OF MONTENEGRO AND SERBIA IN THE FIELD OF INHERITANCE AND ACHIEVING HARMONY IN DECISION-MAKING - Ranković, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In this paper, the legal norms of the private international law of Montenegro and the Republic of Serbia in the field of inheritance are comparatively analysed.Firstly, the legal norms on the international jurisdiction in both states, from the aspect of prevention of positive conflicts of jurisdiction are examined, followed by the analysis of the provisions on determining the applicable law for inheritance. Then, Private International law issues (jurisdiction, applicable law and mutual recognition of decisions) are discussed through six hypothetical factual situations, in order to illustrate the problems of coordination that courts, i.e., notaries in these two countries may face in deciding the cases regarding inheritance with a foreign element. The aim of the paper is to examine whether the differences in the legal norms on international jurisdiction and applicable law have a negative impact on the resolution of inheritance law cases related to two states and to consider possible solutions in order to eliminate this negative impact.